Career counseling and planning - Sushil Kumar Srivastava; Major career options and routes (New Delhi : Atlantic Publishers and Distributers Pvt Ltd, 2011)
Book Review: Career Counseling, Planning and Guiding : This book offers a practical approach to career counseling, particularly for beginners. It effectively balances theoretical concepts with real-world applications, making it accessible to a wide audience. The author's extensive experience in various industries lends credibility to the advice provided. While the book covers a broad range of topics, from career skills to educational opportunities, its strength lies in its focus on Indian scenarios. The detailed information on different career paths and the Indian education system is invaluable for students and job seekers. However, the book could benefit from a more in-depth exploration of emerging career trends and the impact of technology on the job market. Nonetheless, it remains a valuable resource for anyone seeking guidance on career planning and decision-making.
Keywords: Career counseling; Career skills : resumes, interviews, and career change; Indian education system and career paths; Financing higher education